An electrocardiograph tutor using expert system technology - Meyer, Derek Louis (Department of Integrative Biomedical Sciences, 2018)
Computer systems for the interpretation of diagnostic ECGs are widely used, but currently provide no explanatory or teaching functions of value to the less experienced practitioner. The relevant literature is reviewed, and specifications are provided for an ECG analysis system which will function as a learning aid for undergraduate and postgraduate medical students. Key aspects of the specifications are implemented on an IBM-PC. Recommendations for further development are provided.